2019
DOI: 10.3389/fpsyt.2019.00232
|View full text |Cite
|
Sign up to set email alerts
|

Is the Clinical Version of the Iowa Gambling Task Relevant for Assessing Choice Behavior in Cases of Internet Addiction?

Abstract: Objective: A critical issue in research related to the Iowa gambling task (IGT) is the use of the alternative factors expected value and gain–loss frequency to distinguish between clinical cases and control groups. When the IGT has been used to examine cases of Internet addiction (IA), the literature reveals inconsistencies in the results. However, few studies have utilized the clinical version of IGT (cIGT) to examine IA cases. The present study aims to resolve previous inconsistencies and to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Studies using other risky decision-making tasks reported riskier decision making in individuals with tendencies towards sIUD or gaming disorder specifically [34][35][36][37][38][39]. However, other studies reported no behavioral differences [40][41][42]. Decision making and related cognitive processes, such as working memory and attention, are considered impaired in addictive disorders [23,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using other risky decision-making tasks reported riskier decision making in individuals with tendencies towards sIUD or gaming disorder specifically [34][35][36][37][38][39]. However, other studies reported no behavioral differences [40][41][42]. Decision making and related cognitive processes, such as working memory and attention, are considered impaired in addictive disorders [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Using these tasks, studies reported deficient (i.e., riskier) decision making across various psychopathological conditions (for reviews see e.g., [ 4 , 33 ]) including individuals with tendencies towards sIUDs such as gaming disorder [ 34 , 35 , 36 , 37 ] and social-networks-use disorder [ 38 , 39 ] as compared to healthy control groups. However, there were also contradictory findings reporting no significant differences between individuals with sIUD and control groups [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes a stronger preference for smaller sooner over larger later rewards (i.e., have a higher discount rate) [44,45] and weaker (i.e., riskier) performance on gambling tasks that provide objective risk information [46,47]. In decisions under ambiguity, findings are less clear which suggests that decisionmaking performance in this type of situations might not be indicative of GD [48].…”
Section: Neuroscientific and Psychological Findings On Reward Processmentioning
confidence: 99%
“…The Iowa Gambling Task (IGT) is a computerized assessment that presents individuals with realistic gambling decisions, and is used experimentally to investigate normal and disordered decision making and adapted for clinical use (Lin et al, 2019), including for clinical diagnosis of ADHD (Toplak et al, 2010). The task assigns the participant an initial imaginary monetary account, and asks them to select cards from one of four decks, causing a gain or loss from this account.…”
Section: The Iowa Gambling Task As a Behavioral Indicator Of Adhdmentioning
confidence: 99%